Influence of Physical Mixing Ratio on Pore Development in Highly Porous Carbon Prepared From Nipa Palm Husk Using Hydrothermal Carbonization with Chemical Activation. Issue 1 (July 2020) - Dechabun, Sutthinan; Udomsap, Parncheewa; Chollacoop, Nuwong; Eiad-Ua, Apiluck
Abstract: In this study, porous carbon materials were prepared from nipa palm ( Nypa fruiticans ) husk using hydrothermal carbonization process with KOH activation through physical mixing. In order to investigate effects of factors on carbon products, hydrothermal temperature and duraton were set to 180°C and 8 hours, and KOH:hydrochar activation weight ratio at 1:1, 1:2 and 1:3, respectively. Prepared carbon materials then were carbonized at 900°C for 2 hours under nitrogen atmosphere and characterized by scanning electron microscope, fourier-transform infrared spectroscopy and x-ray diffraction. According to the results, carbon material produced using physical mixing activation ratio of 1:1 shows the most significant pore development and surface chemical properties, leads to finding a promising way to prepare environmental-friendly highly porous carbon material from biomass.